HUBUNGAN PENDIDIKAN KARAKTER TERHADAP KEDISIPLINAN SANTRI DI PONDOK PESANTREN AL-HIKMAH MUHAMMADIYAH SUKOHARJO TAHUN AJARAN 2024-2025 - Fatimah, Annisa; Abdullah, Mu'in; Safitri, Yuni (STKIP Pesisir Selatan, 2025)
Objective: This study aims to determine (1) the level of student discipline at Pondok Pesantren Al-Hikmah Muhammadiyah Sukoharjo, (2) the relationship between character education and student discipline, and (3) the quality of character education implemented at the pesantren. This research employed a quantitative approach using a correlational method. The subjects consisted of 20 tenth-grade students in the 2024–2025 academic year. Methods: ]Data were collected through character education and discipline questionnaires and were analyzed using validity and reliability tests, descriptive analysis, and Spearman’s rho correlation test due to the non-normal data distribution. Results: The results show that character education is categorized as high (85%), while student discipline is also categorized as high (75%). The Spearman correlation test produced a value of ρ = 0.673 with sig. 0.001 < 0.05, indicating a strong and significant relationship between character education and student discipline. The coefficient of determination of 45.3% indicates that character education contributes 45.3% to student discipline, while the remaining 54.7% is influenced by other factors. Novelty: Thus, the better the character education implemented, the higher the level of student discipline.